The Post-Secular City The New Secularization Debate - Costa, Paolo (Brill, 2022)
"The Post-Secular City" is the first attempt to systematically map and assess the recent debate about secularization. "The Post-Secular City" examines the alleged shift from a "secular" to a "post-secular" dispensation from the perspective of the ongoing de-construction of the secularization "theorem" (as Hans Blumenberg called it). Accordingly, the new secularization debate is described as being polarized between the "de-constructors" and the "maintainers" of the standard thesis of secularization. This is the assumption underlying an ambitious effort to map the field, which consists of a long introduction where "secularization" is analyzed as a deeply problematic concept-of-process and of eight chapters in which several protagonists of the recent debate are discussed as crucial junctions of a multidisciplinary conversation.